2022
DOI: 10.1108/ijchm-12-2021-1469
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of social media platform image on hotel customers’ visit intention

Abstract: Purpose Many tourism-related industries, such as hotels, use social media as a marketing tool for promotion and distribution. This paper aims to use a model that explores the impact of social media platform image (SMPI) on customers’ visit intention (VI) in a hotel context, using hotel image (HI), motivation (Mot) and anticipated service quality (ASQ) as mediators. The objectives of this study are then: to understand the interactions between the two brand images, to test the mediation effect of HI, Mot and ASQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…Berbekova et al, 2021;Li et al, 2022;Wut et al, 2021). Chen et al (2022) identify that, although previous epidemic research has highlighted consumers' perceptions of risk and associated changes to their travel behavior, potential strategies for ameliorating such behavioral changes while maintaining safety and security have largely been ignored (Ding et al, 2022;Ho et al, 2022;Simonetti and Bigne, 2022). This paper addresses this concern by offering an empirical study in which (1) it is shown that the use of health and safety protocols contributes to the generation of a higher perceived value and intention to visit the hotel (compared to hotels that do not use a health and safety protocol) and ( 2) evaluated the moderating role of the hotel brand awareness on the effects that the use of health and safety protocols on perceived value and the intention to stay at the hotel.…”
Section: Discussionmentioning
confidence: 99%
“…Berbekova et al, 2021;Li et al, 2022;Wut et al, 2021). Chen et al (2022) identify that, although previous epidemic research has highlighted consumers' perceptions of risk and associated changes to their travel behavior, potential strategies for ameliorating such behavioral changes while maintaining safety and security have largely been ignored (Ding et al, 2022;Ho et al, 2022;Simonetti and Bigne, 2022). This paper addresses this concern by offering an empirical study in which (1) it is shown that the use of health and safety protocols contributes to the generation of a higher perceived value and intention to visit the hotel (compared to hotels that do not use a health and safety protocol) and ( 2) evaluated the moderating role of the hotel brand awareness on the effects that the use of health and safety protocols on perceived value and the intention to stay at the hotel.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s findings offer theoretical implications for the hospitality literature. First, this study contributes to research on the consumption of media in the hospitality industry by investigating online reviews from integrated websites and SNS (Ho et al , 2022). Second, to the best of the authors’ knowledge, the present study is the first to integrate the two perspectives of writers and readers simultaneously to provide a holistic view of the online reviews process from production to consumption.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Understanding how readers perceive and interpret online reviews is extremely important for hospitality businesses and tourist destinations, as online consumer reviews influence travelers’ choices (Chatterjee, 2020). For example, readers are motivated to stay at properties after observing images on social media platforms (Ho et al , 2022). The impact of online review is all the more pertinent to the tourism and hospitality businesses because of the complex process of deciding where to stay, how to move, what to eat and where to go (Filieri et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on hotel survival have ignored the crucial internet-related environmental factor of online media coverage. Many hotels conduct online marketing on online media platforms through media coverage and other forms (Ho et al , 2022), which has a non-negligible impact on customers’ behavior and hospitality firm survival. Online news inconsistency can be used as an efficient marketing tool for small and medium-sized hotels to bring brand awareness at a low cost.…”
Section: Discussionmentioning
confidence: 99%